Efek Variasi Konsentrasi Zat Aktivator H3PO4 Terhadap Daya Serap Karbon Aktif Cangkang Kemiri - Kadang, Mytha Rangga Allo Maola; Anas, Muhammad; Mongkito, Vivi Hastuti Rufa (Jurnal Penelitian Pendidikan Fisika, 2020)
This study aims: (1) to determine the effect of variations in the concentration of activator H3PO4 on activated carbon of candlenut shell on iodine adsorption (2) to see the effect of variations in the concentration of H3PO4 activator on the candlenut shell activated carbon on the adsorption of methylene blue. Candlenut shell activated carbon is obtained in three stages of preparation, the carbonization stage uses a pyrolysis reactor for Â± 8 hours with a temperature of 400 0C, the chemical activation stage uses H3PO4 activator with a concentration variation of 29%, 48%, 67%, 85%. Analysis of iodine adsorption using the titrimetric method, while analysis of the adsorption of methylene blue using the spectrophotometric method. The results of the analysis of candlenut shell activated carbon on the adsorption capacity of iodine and methylene blue for each variation of the concentration of H3PO4 activator, namely 591,16 mg/g, 724 mg/g, 777,14 mg/g, 830,28 mg/g, 757, 21 mg/g and the adsorption of methylene blue was 121,84 mg/g, 169,3 mg/g, 200,95 mg/g, 248,42 mg/g, 185,13 mg/g. The result of the analysis of the adsorption of iodine and methylene blue showed that the higher activator concentration, the higher of adsorption of iodine and methylene blue, until it reached a maximum condition at a concentration of 67%. This value meets the SNI.